Determination of the haplotype and complete mitochondrial genome of the rough-toothed dolphin Steno bredanensis (Cetacea: Delphinidae) stranded in Korea. Issue 1 (2nd January 2019) - Park, Seon Young; Cho, Yuna; Lee, JunMo; Lee, Kyunglee; Lim, Se Ra; Seo, Seunghyun; Han, Wonmin; Kim, Hye Kwon; Han, Jee Eun; Kim, Ji Hyung
Abstract: We report the complete mitogenome of a rough-toothed dolphin, Steno bredanensis CRI008296, stranded in Korea. Overall, structure and taxonomical position of the mitogenome were analysed, and its determined haplotype indicated that the same subpopulation is distributed between Korea and Japan.